Distribution of aggregate income in Portugal from 1995 to 2000 within a SAM (Social Accounting Matrix) framework. Modelling the household sector - Santos, Susana (2009)
Aggregated Social Accounting Matrices (SAMs) will be constructed for the Portuguese economy from 1995 to 2000, based on the country's national accounts statistics. The economic flows associated with households, enterprises, government and other institutions will be analysed, as well as their evolution, whilst accounting multipliers will be calculated to facilitate the study of the effects resulting from changes in household income. Therefore, SAMs are modelled and structural path analysis will be used for the decomposition of the calculated multipliers. At the end, the general guidelines will be established for following the study of income distribution and poverty in Portugal.